2004
DOI: 10.1073/pnas.0405557101
|View full text |Cite
|
Sign up to set email alerts
|

A cationic lipid-formulated plasmid DNA vaccine confers sustained antibody-mediated protection against aerosolized anthrax spores

Abstract: DNA vaccines provide an attractive technology platform against bioterrorism agents due to their safety record in humans and ease of construction, testing, and manufacture. We have designed monovalent and bivalent anthrax plasmid DNA (pDNA) vaccines encoding genetically detoxified protective antigen (PA) and lethal factor (LF) proteins and tested their immunogenicity and ability to protect rabbits from an aerosolized inhalation spore challenge. Immune responses after two or three injections of cationic lipidfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
75
1
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(81 citation statements)
references
References 28 publications
4
75
1
1
Order By: Relevance
“…This resulted in high-level expression of H C 50. It might be secreted from host cells using the signal peptide of human tissue plasminogen activator (PLAT) [42,43], and the secretory H C 50 might be presented to antigen-presenting cells (APCs) more efficiently after vaccination. In any case, the vaccine construct was more potent at inducing host immune responses than was an adenoviral vector encoding the native H C 50 sequence (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…This resulted in high-level expression of H C 50. It might be secreted from host cells using the signal peptide of human tissue plasminogen activator (PLAT) [42,43], and the secretory H C 50 might be presented to antigen-presenting cells (APCs) more efficiently after vaccination. In any case, the vaccine construct was more potent at inducing host immune responses than was an adenoviral vector encoding the native H C 50 sequence (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Various formulations have been tested in preparing anthrax vaccines based upon rPA for its ability to elicit optimal immunological responses. Recent examples include Toll-like receptor ligands CpG ODN and Resiquimod R-848 [35,36], pluronic F127, a non-ionic, hydrophilic polyoxyethylenepolyoxypropylene block copolymer [37], additional vaccine antigens such as capsule [38] or EF [39,40], DNA vaccines [41], and mucosal vaccine strategies [42,43]. That antibodies have been recognized as important in protection is demonstrated by the number of immunotherapeutic reagents that have been recently suggested [44][45][46][47][48][49].…”
Section: Effect Of Formaldehyde On Serological Response and Protectionmentioning
confidence: 99%
“…Since 2001, when spores of B. anthracis sent through the U.S. mail resulted in infection in 22 individuals, including 5 fatal cases of inhalation anthrax, significant efforts have been directed toward reevaluating our preparedness for possible bioterrorist threats, including weaponized anthrax. This has included renewed efforts to more critically evaluate the anthrax vaccine currently approved in the United States, BioThrax, as well as continued development of new, alternative vaccines for anthrax (1)(2)(3)(4)(5)(6). We previously showed that immunization of rabbits with a multiple antigenic peptide (MAP), which display multiple copies of a target sequence extending from a branched lysine core, was capable of eliciting antibody specific for a linear determinant in the 2␤2-2␤3 loop, which mediated high-titer neutralization of lethal toxin (LeTx) in vitro (7,8) and protection of rabbits from a targeted aerosol challenge of 200 50% lethal doses (LD 50 ) of B. anthracis Ames strain in vivo (9).…”
mentioning
confidence: 99%